Penerapan Iptek dan Peningkatan Kualitas Produk Aneka Kerupuk dan Keripik di Desa Meteseh, Kecamatan Tembalang, Kota Semarang - Nurkhayati, Isnaini; Sulistiyani, Endang; Winarto; Jumi; Haribowo, Putut; Suratno, Agus; Marhaeni, Sri; Nugroho, Jati (DIKEMAS (Jurnal Pengabdian Kepada Masyarakat), 2022)
The application of science and technology and improving the quality of products to develop a snack business in the business group "Various Crackers and Chips" in the village of Meteseh, Tembalang, Semarang, will have an impact on increasing the income of members of the business group. The business group "Various Crackers and Chips" in Meteseh village in producing its products, still relying on manual labor, less hygienic and less varied and innovative products produced, the benefits obtained from year to year did not experience a significant increase. As educators, they are required to play a role in helping the Government, so the business group "Various Crackers and Chips" in Meteseh village has a better standard of living. In order for the products produced by the business group "Various Crackers and Chips" in Meteseh Village to be more innovative, it is necessary to increase the knowledge and skills that can produce added value, namely learning how to process crackers and chips with a variety of flavors, with more modern equipment and proper packaging procedures so that products are more durable and in demand by the community. The equipment used to process crackers and chips, has been prepared by the Community Service Team. The equipment used in the processing of crackers and chips is as follows: Gas Stove, frying pan, chopper, oil drainer, seasoning mixer, blender, airtight press machine, plastic packaging, ingredients for making crackers and chips etc. Business groups are also given management training and help find solutions to the problems they face. Problems with the problem of partner SMEs are then referred to as a number of program solutions to solve problems in the field of improving production and marketing processes. The method applied is training and mentoring. The output produced is the emergence of " Meteseh Typical Crackers and Chips" business. The value of support from the value added production of Meteseh's unique Crackers and Chips has the potential to become a typical Semarang souvenir from Meteseh village.